PENGARUH CUSTOMER EXPERIENCE, CUSTOMER EXPECTATION TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY D′ BESTO CHICKEN & BURGER - Andria Ningsih; Delfi Hurnis (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to test and analyze how the influence of Customer Experience and Customer Expectation on Customer Satisfaction Customer Loyalty and how the influence of Customer Satisfaction on Customer Loyalty D′ BestO Chicken & Burger in the city of Bukittinggi. The population that will be used as research is consumers who shop at outlets throughout the city of Bukittinggi, totaling 100 people. The sampling technique in this research was carried out by means of a purposive sampling method. In this study the design used was based on data collection methods, namely survey research. The types of data in this study are qualitative and quantitative data. The collected data will be analyzed descriptively and processed using PLS version 4.0. The results of the analysis show that Customer Experience has a significant effect on Customer Satisfaction and Customer Loyalty, Customer Expectation has a significant effect on Customer Satisfaction and Customer Loyalty and Customer Satisfaction has a significant effect on Customer Loyalty.